Protection of the rights of the accused in disciplinary investigations at university personnel - Detkawinlerd, Wuttikon (Journal for Developing the Social and Community, 2021)
Nowadays, University has inquiry process on disciplinary punishment of employees, who is accused to do wrong disciplines, break rules and regulations of university. The inquiry process begins with designation of the inquiry committees in different stages and continues to the procedure of consideration on disciplinary punishment to university employee, who has been accused of acting dishonestly on disciplines. Fact consideration in the inquiry process should be processed sequentially with the following evidences; witness, written evidence and physical evidence. The evidences are applied to investigate the misleading behavior of employees toward university’s disciplines and regulations. Before the disciplinary punishment to the accused, the right of the accused must be protected for justice. This article has presented protection of the rights of the accused during the procedure of inquiry. The procedure plays an important role to perform justified and equitable inquiry process on disciplinary punishment. The rights of the accused must be protected, such as the right on appeal to the committee of disciplinary inquiry, the right to have a lawyer etc. If the inquiry process has rightful protection to the accused, it will have effective result which leads to the equity judgment. In contrast, if the inquiry process is without the procedure of the accused protection, it might destroy the justice and affect university employee who has been accused of acting dishonestly on disciplines.